New chromatographic and data evaluation approaches for the comprehensive investigation of metal-phytosiderophore-complex dynamics - Laura Zellner; Andreea Spiridon; Sangeeta Kumari; Simone Braeuer; Nicolas Kratena; Christian Stanetty; Eva Oburger; Tim Causon; Christian W. Klampfl; Stephan Hann (Analytica Chimica Acta, 2026)

Rapid quantitative bioanalysis using LC-HRIM-QTOFMS with flexible sample delivery and variable traveling wave profiles - Sabrina M. Cramer; Viktoria Kowarz; Diethard Mattanovich; Stephan Hann; Tim Causon (Analytica Chimica Acta, 2026)

Phytosiderophore pathway response in barley exposed to iron, zinc or copper starvation - David Aleksza; Andreea Spiridon; Mika Tarkka; Marie-Theres Hauser; Stephan Hann; Tim Causon; Nicolas Kratena; Christian Stanetty; Timothy S. George; Joanne Russell; Eva Oburger (Plant Science, 2024)

Surveying the mugineic acid family: Ion mobility – quadrupole time-of-flight mass spectrometry (IM-QTOFMS) characterization and tandem mass spectrometry (LC-ESI-MS/MS) quantification of all eight naturally occurring phytosiderophores - Andreea Spiridon; Eva Oburger; Younes Valadbeigi; Tobias Kloimböck; Christian Stanetty; Nicolas Kratena; Markus Draskovits; Tim Causon; Stephan Hann (Analytica Chimica Acta, 2023)

Non-targeted analysis with high-resolution mass spectrometry for investigation of riverbank filtration processes - Kaan Georg Kutlucinar; Sebastian Handl; Roza Allabashi; Tim Causon; Christina Troyer; Ernest Mayr; Reinhard Perfler; Stephan Hann (Environmental Science and Pollution Research, 2022)
A fully non-targeted analytical workflow for the investigation of a riverbank filtration site located at the river Danube has been developed and applied. Variations of compound intensities at different sampling locations of the riverbank filtration site and, for a single production well, over a monitoring period of one year have been investigated using liquid chromatography combined with time-of-flight-mass spectrometry followed by evaluation via non-targeted data analysis. Internal standardization and appropriate quality control strategies have been implemented into the workflow for reduction of possible methodological biases influencing data interpretation. Emphasis was placed on the assessment of different blank elimination steps and the final blank elimination strategy is reported. The spatial study of the selected riverbank filtration site revealed a homogenous composition of the filtered water sampled at 11 different locations across the 32,000 m 2 site, except for one sampling location in a zone of the aquifer, which was only weakly connected to the well field in terms of hydrogeological conditions. The examination of time-dependent changes of the composition of surface and groundwater obtained at the riverbank filtration system revealed that the non-targeted workflow is fit-for-purpose regarding the assessment the stability of filtration efficiency and compound residence time in the riverbank filtration compartment. In total, 677 compounds were selected for the investigation of the time-dependent variations of the filtration process. Analysis of the signal intensities of these compounds revealed that the riverbank filtration is significantly reducing the intensity and number of compounds present in surface water over a wide polarity range. In addition, the method enabled the determination of compound residence times in the riverbank filtration system ranging from 5 to 7 days.

Correction to: LC–MS based metabolic fingerprinting of apricot pistils after self-compatible and self-incompatible pollinations - József Lénárt; Attila Gere; Tim Causon; Stephan Hann; Mihály Dernovics; Olga Németh; Attila Hegedűs; Júlia Halász (Plant Molecular Biology, 2021)

LC–MS based metabolic fingerprinting of apricot pistils after self-compatible and self-incompatible pollinations - József Lénárt; Attila Gere; Tim Causon; Stephan Hann; Mihály Dernovics; Olga Németh; Attila Hegedűs; Júlia Halász (Plant Molecular Biology, 2021)
Key message LC-MS based metabolomics approach revealed that putative metabolites other than flavonoids may significantly contribute to the sexual compatibility reactions in Prunus armeniaca . Possible mechanisms on related microtubule-stabilizing effects are provided. Abstract Identification of metabolites playing crucial roles in sexual incompatibility reactions in apricot ( Prunus armeniaca L.) was the aim of the study. Metabolic fingerprints of self-compatible and self-incompatible apricot pistils were created using liquid chromatography coupled to time-of-flight mass spectrometry followed by untargeted compound search. Multivariate statistical analysis revealed 15 significant differential compounds among the total of 4006 and 1005 aligned metabolites in positive and negative ion modes, respectively. Total explained variance of 89.55% in principal component analysis (PCA) indicated high quality of differential expression analysis. The statistical analysis showed significant differences between genotypes and pollination time as well, which demonstrated high performance of the metabolic fingerprinting and revealed the presence of metabolites with significant influence on the self-incompatibility reactions. Finally, polyketide-based macrolides similar to peloruside A and a hydroxy sphingosine derivative are suggested to be significant differential metabolites in the experiment. These results indicate a strategy of pollen tubes to protect microtubules and avoid growth arrest involved in sexual incompatibility reactions of apricot.